Tryptophan metabolism in the central nervous system: medical implications. - Ruddick,JP; Evans,AK; Nutt,DJ; Lightman,SL; Rook,GAW; Lowry,CA (Expert Rev Mol Med, 2006)
The metabolism of the amino acid L-tryptophan is a highly regulated physiological process leading to the generation of several neuroactive compounds within the central nervous system. These include the aminergic neurotransmitter serotonin (5-hydroxytryptamine, 5-HT), products of the kynurenine pathway of tryptophan metabolism (including 3-hydroxykynurenine, 3-hydroxyanthranilic acid, quinolinic acid and kynurenic acid), the neurohormone melatonin, several neuroactive kynuramine metabolites of melatonin, and the trace amine tryptamine. The integral role of central serotonergic systems in the modulation of physiology and behaviour has been well documented since the first description of serotonergic neurons in the brain some 40 years ago. However, while the significance of the peripheral kynurenine pathway of tryptophan metabolism has also been recognised for several decades, it has only recently been appreciated that the synthesis of kynurenines within the central nervous system has important consequences for physiology and behaviour. Altered kynurenine metabolism has been implicated in the pathophysiology of conditions such as acquired immunodeficiency syndrome (AIDS)-related dementia, Huntington's disease and Alzheimer's disease. In this review we discuss the molecular mechanisms involved in regulating the metabolism of tryptophan and consider the medical implications associated with dysregulation of both serotonergic and kynurenine pathways of tryptophan metabolism.